2016
DOI: 10.1080/01694243.2016.1192011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peel angle on peel force of adhesive tape from soft adherend

Abstract: In the case of the peeling of adhesive tapes from soft adherends, the contributions of the compressive force at the adhered portion as well as the larger deformation of adherend have essential roles in determining the peeling properties. In this paper, the peel force of an adhesive tape from a soft adherend has been measured to understand the peeling mechanism, which is greatly affected by the peel angle. A commercially available pressure-sensitive adhesive was used as the tape, and a cross-linked polydimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For the separation force to equal the adhesion force, it is required that the analogy to Tate's law will be insensitive to the direction of the separation process, since the liquid−liquid separation is vertical to the solid−liquid separation. Such a requirement is justified if we consider adhesion studies done on adhesive tapes 34 where the peeling force is insensitive to the peeling direction for tapes with low elastic modulus. Yet, more studies are needed to address it theoretically.…”
Section: ■ Theorymentioning
confidence: 99%
“…For the separation force to equal the adhesion force, it is required that the analogy to Tate's law will be insensitive to the direction of the separation process, since the liquid−liquid separation is vertical to the solid−liquid separation. Such a requirement is justified if we consider adhesion studies done on adhesive tapes 34 where the peeling force is insensitive to the peeling direction for tapes with low elastic modulus. Yet, more studies are needed to address it theoretically.…”
Section: ■ Theorymentioning
confidence: 99%
“…It is experimentally demonstrated that higher peel rates cause higher peel force 25,3941 . The primary reason is changing the effective length of cohesive zone in the adhesive layer which is changing dramatically by the peel rate.…”
Section: Resultsmentioning
confidence: 99%
“…At higher concentrations than 0.4 wt %, both hydrogels with 9 and 18 kPa of elastic modulus were broken before the detachment at the glued area because PDMA hydrogels are weaker than the nanoparticle-mediated bridge. Therefore, a 90° peel test was performed to measure the adhesion energy produced at a higher concentration of deposited solutions. Using the same 9 kPa PDMA hydrogels, the 90° peeling test was performed at a constant speed of 150 mm/min, as described in Figure a.…”
Section: Results and Discussionmentioning
confidence: 99%